A Plant-Produced Virus-Like Particle Displaying Envelope Protein Domain III Elicits an Immune Response Against West Nile Virus in Mice - Stander, Jennifer; Chabeda, Aleyo; Rybicki, Edward P.; Meyers, Ann E. (Frontiers in Plant Science, 2021)
West Nile virus (WNV) is a globally disseminated flavivirus that is associated with encephalitis outbreaks in humans and horses. The continuous global outbreaks of West Nile disease in bird, human and horse populations, with no preventative measures for humans, pose a major public health threat. The development of a vaccine that contributes to the ‘One Health’ Initiative could be the answer to prevent the spread of the virus and control human and animal disease. The current commercially available veterinary vaccines are generally costly, and most require high levels of biosafety for their manufacture. Consequently, we explored making a particulate vaccine candidate made transiently in plants as a more cost-effective and safer means of production. A WNV virus-like particle-display based vaccine candidate was generated by use of the SpyTag/SpyCatcher conjugation system. The WNV envelope protein domain III (EDIII), which contains WNV-specific epitopes, was fused to and displayed on AP205 phage virus-like particles (VLPs) following the production of both separately in Nicotiana benthamiana. Co-purification of AP205 and EDIII genetically fused to SpyTag and SpyCatcher, respectively, resulted in conjugated VLPs displaying EDIII with an average coupling efficiency of 51%. Subcutaneous immunization of mice with 5 µg of purified AP205:EDIII VLPs elicited a potent IgG response to WNV EDIII. This work presents the potential plants have of being used as biofactories for making significant pharmaceutical products for the ‘One Health’ Initiative and could be used to address the need for their local production in LMICs.